Facile Fabrication of a Hierarchical Superhydrophobic Coating with Aluminate Coupling Agent Modified Kaolin. (4th November 2013) - Li, Hui; Qu, Mengnan; Sun, Zhe; He, Jinmei; Zhou, Anning
Abstract : A superhydrophobic coating was fabricated from the dispersion of unmodified kaolin particles and aluminate coupling agent in anhydrous ethanol. Through surface modification, water contact angle of the coating prepared by modified kaolin particles increased dramatically from 0° to 152°, and the sliding angle decreased from 90° to 3°. Scanning electron microscopy was used to examine the surface morphology. A structure composed of micro-nano hierarchical component, combined with the surface modification by aluminate coupling agent which reduced the surface energy greatly, was found to be responsible for the superhydrophobicity. The method adopted is relatively simple, facile, and cost-effective and can potentially be applied to large water-repellent surface coatings.